Music Interventions for Dementia and Depression in ELderly care (MIDDEL): protocol and statistical analysis plan for a multinational cluster-randomised trial. Issue 3 (30th March 2019) - Gold, Christian; Eickholt, Jasmin; Assmus, Jörg; Stige, Brynjulf; Wake, Jo Dugstad; Baker, Felicity Anne; Tamplin, Jeanette; Clark, Imogen; Lee, Young-Eun Claire; Jacobsen, Stine Lindahl; Ridder, Hanne Mette Ochsner; Kreutz, Gunter; et al.
Abstract : Introduction: In older adults, dementia and depression are associated with individual distress and high societal costs. Music interventions such as group music therapy (GMT) and recreational choir singing (RCS) have shown promising effects, but their comparative effectiveness across clinical subgroups is unknown. This trial aims to determine effectiveness of GMT, RCS and their combination for care home residents and to examine heterogeneity of treatment effects across subgroups. Methods and analysis: This large, pragmatic, multinational cluster-randomised controlled trial with a 2×2 factorial design will compare the effects of GMT, RCS, both or neither, for care home residents aged 65 years or older with dementia and depressive symptoms. We will randomise 100 care home units with ≥1000 residents in total across eight countries. Each intervention will be offered for 6 months (3 months 2 times/week followed by 3 months 1 time/week), with extension allowed if locally available. The primary outcome will be the change in the Montgomery-Åsberg Depression Rating Scale score at 6 months. Secondary outcomes will include depressive symptoms, cognitive functioning, neuropsychiatric symptoms, psychotropic drug use, caregiver burden, quality of life, mortality and costs over at least 12 months. The study has 90% power to detect main effects and is also powered to determine interaction effects with gender, severity and socioeconomic status. Ethics and dissemination: Ethical approval has been obtained for one country and will be obtained for all countries. Results will be presented at national and international conferences and published in scientific journals. Trial registration numbers: NCT03496675; Pre-results, ACTRN12618000156280.